TO STUDY THE EFFICACY OF RASA PARPATI WITH JATYADI GHRITA MATRA BASTI IN THE MANAGEMENT OF ULCERATIVE COLITIS - Shekokar, Anantkumar; Borkar, Kanchan; Kumar Singh, Ashish (International Journal of Ayurveda and Pharma Research, 2015)
The ulcerative colitis is a specific and non-specific inflammatory disease of large bowel, which is usually confined to its mucosa, presents with remissions and exacerbations where, the pathetical changes are usually restricted to mucosa except in very severe acute attacks of the disease when they reach into the deeper layers of the bowel wall. Colitis is an acute, subacute, or chronic disease of the colon and rectum of variable etiology, course and unpredictable prognosis. Bhaishajya Chikitsa is one of the treatment modalities of the Raktaatisar (ulcerative colitis) given by Ayurved literature which is also very effective like other treatment modalities. Also people have now turned their faith towards Ayurveda to resolve their health problems and hence most of cases perusable conservative treatment as it is more economical, painless, no hospitalization is required and no complications observed during or after medication. Modern medicine has limited source of medical treatment such as temporary medication with intestinal antibiotics, anti diarrhoeal, salazopyrine, steroids, immune modulator drugs and lastly surgery. Keeping all these facts in mind a clinical study was designed on the basis of Sampraptivighatana Chikitsha, for ulcerative colitis. Rasa Parpati & Jatyadi Ghrita having disease modifying potential and a good safely profile should thus be evaluated for use in this disease condition. The clinical study has been done on 60 patients, selected randomly and divided in two groups. Group A i.e trial group patients were treated with oral dose of Rasa Parpati & Jatyadi Ghrita Matra Basti. The Group B patients i.e. control group, were treated with Salazopyrine. The clinical assessment was done on the basis of clinical presentation of ulcerative colitis as well as colonoscopic findings, before and after the treatment. The findings of the study have been statistically analysed with the help of t-test and the result of the study found significant.